Personality traits and preferences for specialty coffee: Results from a coffee shop field experiment. (November 2019) - Ufer, Danielle; Lin, Wen; Ortega, David L.
Abstract: The market for specialty coffee is growing as consumer preferences for high quality coffee become more complex. Identifying the sources of heterogeneity in consumer preferences for specialty coffee is essential to optimizing producer marketing strategies to ensure they both fully capitalize on and satisfy consumer demand. One source of increasing interest is consumer personality profiles, specifically those categorized by the Big Six personality traits. We use the Midlife Development Inventory to investigate the effect of consumer personality traits on willingness to pay for coffee produced by farmer cooperatives. Results from a field experiment using a Becker-DeGroot-Marschak mechanism indicate that, on average, consumers are willing to pay a $1.31 premium for a cup of pour over coffee that was produced by a cooperative member farmer. Consumers exhibiting the extraversion and conscientiousness traits were, on average, willing to pay an even higher premium while those with higher levels of agency had a lower willingness to pay. Results further highlight that sociodemographic characteristics do not always drive consumer purchase decisions and, in the absence of significant sociodemographic influence, intrinsic consumer characteristics like personality traits can better explain preferences. Graphical abstract: Unlabelled Image Highlights: Personality traits influence preferences for specialty coffee. Consumers are willing to pay premiums for coffee produced by farmer cooperatives. Extraversion and conscientiousness increase preference for cooperative-grown coffee. Agency decreases willingness to pay for cooperative-grown coffee.